Flemingins G−O, Cytotoxic and Antioxidant Constituents of the Leaves of Flemingia grahamiana - Gumula, Ivan; Alao, John Patrick; Ndiege, Isaiah Omolo; Yenesew, Abiy; Erdélyi, Máté (Journal of Natural Products, 2014)
The known flemingins A–C (1–3) and nine new chalcones, named flemingins G–O (4–12), along with deoxyhomoflemingin (13) and emodin (14) were isolated from a leaf extract of Flemingia grahamiana. The isolated chalcones were found to have a geranyl substituent modified into a chromene ring possessing a residual chain, as shown by spectroscopic methods. The leaf extract showed an IC50 value of 5.9 μg/mL in a DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay. The chalcones flemingins A, B, C, G, and H were active in the DPPH radical scavenging assay (ED50 4.4–8.9 μM), while flemingins A and C showed cytotoxicity against MCF-7 human breast cancer cells (IC50 8.9 and 7.6 μM, respectively).